An Offline SEO (Search Engine Optimization) Based Algorithm to Calculate Web Page Rank According to Different Parameters (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
SEO stands for Search Engine Optimization. It is a technique that searches various web pages for specified keywords and ranks these Web pages according to some parameters. They are used to feed pages to search engines. Â The main importance of SEO is that it helps to find the relevant data and increase the rank of a webpage in search enginesâ€™ results. In our paper, we develop a new algorithm M-HITS (Modified HITS) to provide the page rank. M-HITS Algorithm is a new version of HITS algorithm. It is developed by extending the properties of HITS algorithm.